Political Campaign Debates Reconciling Public, Media, and Candidate Needs - Kay, Jack. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
The public, the media, and the candidates each bring a unique and sometimes contradictory set of needs to the political campaign debate that must be reconciled in designing formats to significantly improve debate practice. Five format suggestions address problems characteristic of debates, particularly at the state and local levels: (1) format designers should implement techniques that feature direct clash; (2) designers should seek formats that develop more systematically the issue and policy differences between candidates; (3) designers and questioners should develop more rigorous methods for selecting questions; (4) designers and questioners should provide follow up periods for candidates to push each other to address the questions; (5) debate reporters should strive to provide balanced coverage and avoid instantaneous analysis; and (6) candidates should be given equal time to answer questions and confront one another. (HTH)
ERIC Note: Paper presented at the Annual Meeting of the Speech Communication Association (69th, Washington, DC, November 10-13, 1983).
Microfiche.
Keywords: Competition; Debate; News Media; Persuasive Discourse; Political Attitudes; Political Issues; Politics; Public Speaking; Debate Format -- Political Candidates; Media Role -- Political Campaigns; Opinion Papers; Speeches/Meeting Papers